Peningkatan Kompetensi Guru dalam Implementasi Konsep dan Praktik Perhitungan Pajak PPh Orang Pribadi di Jakarta - Vinola Herawaty; Rukmini Windiarti Soebadio; Liem Yan Sugondo (Penerbit Goodwood, 2021)
Purpose: The purpose of this community service (PKM) is to improve understanding and ability related to the concept and implementation of personal PPh Tax calculations for teachers. Method: This PKM activity is carried out using the tutorial method and discussion on the concept of Personal Income Tax. The target of these trainees is high school teachers under Masyarakat Profesi Teknisi Akuntansi (MATA) Indonesia. The implementation of this training activity is intended to increase the participation of the Program Pendidikan Profesi Akuntan FEB Usakti in helping to improve human resource competence, especially for high school teachers. This activity was carried out on February 18, 2021 online through Zoom Meeting. Results: Based on the evaluation, after following this PKM (1) The participants understand the basic concepts of personal income tax taxation, especially filling out the SPT 1770S for employee.(2). Participants can understand the tax reporting obligations for WPOP.and (3). The participants can fill out/make and report the personal income tax return. Conclusions: There are improvements of teacher competence in terms of the Implementation of the Concept and Practice of Calculation of Personal Income Tax for teachers under the Indonesian Accounting Technician Society (MATA INDONESIA) who play an active role in improving the competence of educators, especially teachers with expertise in tax accounting.